1983
DOI: 10.1002/bjs.1800700510
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy and infection in Hodgkin's disease

Abstract: The incidence of infection in 56 patients with Hodgkin's disease who had undergone staging laparotomy with splenectomy was compared with that of 28 non-splenectomized patients with Hodgkin's disease treated concurrently. The results suggest that splenectomy does not result in a major change in the incidence of infection experienced by such patients with stage II or stage III disease. Aggressive therapy may be of greater importance in increasing the susceptibility to infection in Hodgkin's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Individuals without a spleen run an increased risk of overwhelming infection with high case-fatality for several years after splenectomy (1,(3)(4)(5)(6)(7)(8)(9). More than half these severe infections are due to pneumococci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals without a spleen run an increased risk of overwhelming infection with high case-fatality for several years after splenectomy (1,(3)(4)(5)(6)(7)(8)(9). More than half these severe infections are due to pneumococci.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of staging laparotomy with splenectomy in Hodgkin's disease patients in 1969, many reports have focused upon serious postsplenectomy infections (4)(5)(6)(7)(8)(9). When 145 reported postsplenectomy infections in 115 patients were reviewed (7), most cases presented as pneumonia, septicaemia, meningitis or combinations thereof, the most common offending organism being the pneumococcus.…”
Section: Foss Abrahamsen Et Almentioning
confidence: 99%
“…The incidence of infections was, however, significantly higher in more advanced disease (Abrahamsen et al , 1990). In a study of 84 patients, Keel et al (1983) suggested that aggressive therapy was of greater importance than splenectomy for the risk of infections. In the present study, conducted on 453 patients and with a median follow up of 22·0 years, chemotherapy did not affect the long‐term risk for infections.…”
Section: Risk For Developing Serious Infection Requiring Admission Tmentioning
confidence: 99%